Diaphragm function in acute respiratory failure and the potential role of phrenic nerve stimulation. Issue 3 (June 2021) - Reardon, Peter M.; Wong, Jenna; Fitzpatrick, Aisling; Goligher, Ewan C.
Abstract : Purpose of review: The aim of this review was to describe the risk factors for developing diaphragm dysfunction, discuss the monitoring techniques for diaphragm activity and function, and introduce potential strategies to incorporate diaphragm protection into conventional lung-protective mechanical ventilation strategies. Recent findings: It is increasingly apparent that an approach that addresses diaphragm-protective ventilations goals is needed to optimize ventilator management and improve patient outcomes. Ventilator-induced diaphragm dysfunction (VIDD) is common and is associated with increased ICU length of stay, prolonged weaning and increased mortality. Over-assistance, under-assistance and patient-ventilator dyssynchrony may have important downstream clinical consequences related to VIDD. Numerous monitoring techniques are available to assess diaphragm function, including respiratory system pressures, oesophageal manometry, diaphragm ultrasound and electromyography. Novel techniques including phrenic nerve stimulation may facilitate the achievement of lung and diaphragm-protective goals for mechanical ventilation. Summary: Diaphragm protection is an important consideration in optimizing ventilator management in patients with acute respiratory failure. The delicate balance between lung and diaphragm-protective goals is challenging. Phrenic nerve stimulation may be uniquely situated to achieve and balance these two commonly conflicting goals.